2011
DOI: 10.1108/10309611111163718
|View full text |Cite
|
Sign up to set email alerts
|

Class absenteeism: reasons for non‐attendance and the effect on academic performance

Abstract: Purpose -Other business education literature, particularly in the field of economics, has developed theories in respect of the reasons for non-attendance of lectures and the positive correlation between class attendance and academic performance. The aim of this study was to determine the generalizability of these theories to a large accounting class in South Africa.Design/methodology -This paper is a differentiated replication of the study by Paisey and Paisey (2004), who provided initial evidence of the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…While the aforementioned studies found a positive relationship, a small number of studies did not find any relationship between student performance and attendance (Browne et al, 1991;Schmulian and Coetzee, 2011). The literature discussed above indicates that attendance alone may not be a key driver in relation to student performance; but there may be some relationship to it.…”
Section: Student Attendance and Performancementioning
confidence: 84%
See 1 more Smart Citation
“…While the aforementioned studies found a positive relationship, a small number of studies did not find any relationship between student performance and attendance (Browne et al, 1991;Schmulian and Coetzee, 2011). The literature discussed above indicates that attendance alone may not be a key driver in relation to student performance; but there may be some relationship to it.…”
Section: Student Attendance and Performancementioning
confidence: 84%
“…While attendance alone may (Marburger, 2006;Paisey and Paisey, 2004;Romer, 1993) or may not (Browne et al, 1991;Schmulian and Coetzee, 2011) lead to better student performance, formative feedback has been found to have a positive relationship (Collett, Gyles and Hrasky, 2007;Smith, 2009a, 2009b).…”
Section: Hypothesis Developmentmentioning
confidence: 93%
“…Some of the reasons cited in the literature are illness, tiredness, prioritising other academic work, anticipation of low academic gain, lack of interest/motivation, finding the class boring and "personal reasons" (Cohall & Skeete, 2012;Dollinger, Matyja, & Huber, 2008;Moore, Armstrong, & Pearson, 2008;Paisley & Paisley, 2004;Schmulian & Coetzee, 2011;Woodfield, Jessop, & McMillan, 2006). One reason for student absenteeism might be the availability of online material, including the streaming of lectures.…”
Section: Introductionmentioning
confidence: 99%
“…It would be pertinent to discuss about 'Teaching' and the role of teachers' in this respect. Schmulian and Coetzee (2011) have emphasized the importance of teaching style, and accountability of the 'appropriateness of their style of pedagogy' for the results tro ascertain the 'value addition' in classroom. They highlighted the vested interests of the stakeholders in a student's academic performance and that they pay attention to the "indicators demonstrating the possible value being added by a student's class attendance'.…”
Section: Introductionmentioning
confidence: 99%